2023
DOI: 10.1002/jssc.202200824
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of nine compounds in Fangwen Jiuwei decoction by liquid chromatography–mass spectrometry

Abstract: Fangwen Jiuwei Decoction is a traditional Chinese medicine preparation for the treatment of pneumonia developed by Shenzhen Bao'an Chinese Medicine Hospital, which shows remarkable clinical responses. Qualitative and quantitative analyses of the main active compounds are crucial for the quality control of traditional Chinese medicine prescription in clinical application. In this study, we identified nine active compounds essential for the pharmacological effects of Fangwen Jiuwei Decoction based on the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We employed network pharmacology to explore the correlation between the 7 identified compounds and their anti-PCOS activity [26][27][28][29]. According to PPI analysis, the core targets were inputted into the network visualization software Cytoscape 3.9.0 to build the network (Figure 3) which had 51 nodes and 480 edges.…”
Section: Explore the Anti-polycystic Ovary Syndrome Activity Of Targe...mentioning
confidence: 99%
“…We employed network pharmacology to explore the correlation between the 7 identified compounds and their anti-PCOS activity [26][27][28][29]. According to PPI analysis, the core targets were inputted into the network visualization software Cytoscape 3.9.0 to build the network (Figure 3) which had 51 nodes and 480 edges.…”
Section: Explore the Anti-polycystic Ovary Syndrome Activity Of Targe...mentioning
confidence: 99%
“…CKD incidence is increasing globally and has become a major public health burden [4,5]. Current treatments for CKD are limited; thus, many patients seek alternative therapies, such as traditional Chinese medicine (TCM) [6,7]. Several basic and clinical studies have confirmed that TCM protects kidney function and delays CKD progression [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The working schematic diagram is shown in Figure 1. Though it seemed a routine strategy in the TCMP study [15, 16], special improvement and innovation were conducted in this study according to the concrete circumstances of MTZSFG. Liquid–liquid extraction was introduced into the sample pretreatment process to obtain fractions of different polarities, which were analyzed separately in order to overcome the complexity of components in MTZSFG formulation.…”
Section: Introductionmentioning
confidence: 99%